ENHANCING TEACHER QUALITY FOR EFFECTIVE TEACHING AND LEARNING OF SOCIAL STUDIES AT THE UPPER BASIC EDUCATION LEVEL - Mezieobi, D.I.; Mezieobi, S.A.; Anyanwu, Jerome (Advances in Social Sciences Research Journal, 2017)
Enhancing quality of social studies teacher is significantly necessary for effective teaching and learning of social studies at the upper basic schools in Nigeria. The need to enhance social studies teacher quality are addressed as: defective implementation of social studies, poor-performance of students, dynamics changes, institutionalization of social studies and functional education delivery. Strategies for enhancing social studies teacher quality are presented as follows: Qualitative training of social studies teachers, continuous professional development, employment of professionally trained social studies teachers, quality teaching and effective publications and designing of materials for effective teaching. The envisaged constraints, conclusion and recommendations are highlighted. Keywords: Teacher quality, effective teaching and learning, social studies.